2022
DOI: 10.1002/iis2.12868
|View full text |Cite
|
Sign up to set email alerts
|

Human‐Systems Integration of Agricultural Machinery in Developing Economy Countries: Perceptions of Adoption

Abstract: Widespread adoption of agricultural machinery for developing economy countries is commonly regarded as a fundamental component of pro‐poor growth. This study evaluates agricultural practices using a Human‐Systems Integration approach to more effectively adapt technologies to satisfy farmers’ needs. Six farms in Sudan, Africa were surveyed regarding their opinions towards using farming machinery, were then provided a tractor, and surveyed again after using the tractor for the planting season. The largest barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…While the significance of new agricultural methods in alleviating poverty in developing nations is widely acknowledged, their adoption has frequently been sluggish, with numerous challenges remaining incompletely understood [20]. This underscores the complexity inherent in defining technology adoption, as it hinges on individual acceptance and adoption of the technology [20].…”
Section: Geographic Scopementioning
confidence: 99%
See 1 more Smart Citation
“…While the significance of new agricultural methods in alleviating poverty in developing nations is widely acknowledged, their adoption has frequently been sluggish, with numerous challenges remaining incompletely understood [20]. This underscores the complexity inherent in defining technology adoption, as it hinges on individual acceptance and adoption of the technology [20].…”
Section: Geographic Scopementioning
confidence: 99%
“…Given the impressive capabilities of ICTs outlined by the literature, many limitations exist. Smallholder farmers in developing nations frequently encounter barriers to the adoption of new technologies [20]. The major obstacle lies in balancing the financial and social objectives of farmers [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that farm size is a significant factor in determining the speed of technology adoption (Bonabana-Wabbi, 2002;Lavison, 2013). The relationship between farm size and the adoption of agricultural technology is well documented (Ahmed & Bagchi, 2004;Gabre-Madhin & Haggblade, 2004;Kasenge, 1998;Uaiene, 2009). Generally, larger farms are more likely to adopt new technologies as they have the resources to set aside a portion of their land for research purposes (Uaiene, 2009).…”
Section: Factors Related To Farmers Economic Situationsmentioning
confidence: 99%
“…These shifts in perception of farming for a living, particularly in the reluctance of younger generations to farm, have led to rural out-migration [9], particularly where younger generations are moving out of World 2023, 4 rural areas towards cities. In an interview study with six Sudanese farms, Ahmed and Miller [10] reported that three of the six farms expressed concerns that their children were considering moving to the city in pursuit of another lifestyle. Rural out-migration has further exasperated labor scarcity, leading to increasing labor costs, which is particularly challenging for cash-constrained smallholder farmers [11].…”
Section: Introductionmentioning
confidence: 99%